Application of the Indonesian Realistic Mathematics Education Approach to Improve Student Learning Outcomes - Irawan, Dani; Syarif, Muhammad Ilham; Fidiawati, Liza; Darwati, Darwati; Yulia, Sispa (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This research aims to analyze the effectiveness of implementing the Indonesian Realistic Mathematics Education Approach (PMRI) in improving student learning outcomes in mathematics subjects. PMRI is a learning approach that emphasizes the use of real contexts and daily experiences as a basis for developing mathematical concepts, so that students can more easily understand and relate the subject matter to their real lives. The research method used is classroom action research (PTK) which is carried out in several cycles, each cycle consisting of planning, implementation, observation and reflection. The subjects of this research were class students randomly selected from an elementary school in Indonesia. Data was collected through learning results tests, observations, and interviews with students and teachers. The increase in student learning outcomes is known from the percentage of completion of the evaluation test results in cycle I and cycle II. At the beginning (Pre-cycle) the percentage of student completion was 33.33% (five students) out of fifteen students. In cycle I, the percentage of student completion increased to 66.67% (ten students). Meanwhile, in cycle II, student completion increased to 93.33% (fourteen students) from fifteen students and only one student did not complete. 2) Student learning activities have increased and reached good criteria. Thus, it can be said that research through the application of the Indonesian Realistic Mathematics Education Approach (PMRI) on the material on the properties of flat shapes in class V of Tahfidz Rahmatul Aisy Arosuka Elementary School, Solok Regency was declared successful.